Functional heterogeneity in allospecific cytotoxic T lymphocyte clones. I. CTL clones express strong anti-self suppressive activity (The Rockefeller University Press, 1984)
Five out of five allo-specific cytotoxic T lymphocyte (CTL) clones tested strongly suppressed the development of CTLs directed against the H-2 haplotype of the CTL clone and independent of the H-2 specificity recognized by the CTL clone. This was shown by including 100-1,000 cells from the five clones in one way mixed lymphocyte reaction (MLR) cultures in which the stimulator cells were of the same H-2 type as the CTL cells. When these cultures were assayed for cytotoxicity against the stimulator cell haplotype, the cytotoxic activity was decreased in a CTL cell dose-dependent manner by 50 to more than 90%. Suppression was usually not observed in MLR cultures where the CTL-H-2 type was identical with the responder cells or was different from both the responder or stimulator cells. Suppression was demonstrated not to be due to "cold" target inhibition at the time of cytotoxicity assay. Even if the added CTL were completely removed after 48-72 h of culture, significant suppression was obtained. Suppressive ability did not appear to be correlated with the level of allo-specific cytotoxic activity present in the CTL clones, but might involve direct killing of MLR precursor cells by cells in the added CTL clones. The suppression observed here, which is anti-self from the point of view of the added CTL clone, appears to be triggered by precursor cells in the MLR responder population recognizing MHC determinants on cells from the added CTL clone. This peculiar type of suppression, in which the regulator regulates on being recognized, has been christened the veto phenomenon and may play a role in maintenance of self tolerance.